2015
DOI: 10.5489/cuaj.2447
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic signet-ring cell carcinoma of the urinary bladder: A novel management approach to a rare tumor.

Abstract: Primary signet-ring cell carcinoma (SRCC) of the urinary bladder, a variant of adenocarcinoma, is exceedingly rare and as a result no gold standard exists for its management. We report a case of primary SRCC of the bladder with recurrent metastases; we utilized an innovative diagnostic approach and the patient exhibited a treatment response to palliative FOLFOX-6 chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…6 When encountering bladder SRCC, metastasis from another site, commonly the gastrointestinal tract, should be ruled out. 8 In conclusion, we describe CSF cytology and brain histologic findings of metastatic primary bladder SRCC. A distinctive primary bladder SRCC immunoprofile has not yet been described.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…6 When encountering bladder SRCC, metastasis from another site, commonly the gastrointestinal tract, should be ruled out. 8 In conclusion, we describe CSF cytology and brain histologic findings of metastatic primary bladder SRCC. A distinctive primary bladder SRCC immunoprofile has not yet been described.…”
Section: Discussionmentioning
confidence: 85%
“…This patient with lymph node and spinal metastasis responded well to a modified FOLFOX-6 regimen commonly used to treat metastatic gastrointestinal malignancies. 8 In conclusion, we describe CSF cytology and brain histologic findings of metastatic primary bladder SRCC. This unique complication proved to be rapidly progressive and fatal.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…SRC adenocarcinoma is rare. In consequence, it was virtually exclusively addressed in small‐scale, institutional case series . The exception consists of the study of Wang et al .…”
Section: Discussionmentioning
confidence: 99%
“…In consequence, it was virtually exclusively addressed in small-scale, institutional case series. 8,29,30 The exception consists of the study of Wang et al that relied on the SEER registry covering years 1973-2004, where authors identified 103 SRC patients of all stages, including those with distant metastases, who were exposed to a wide variety of treatment modalities, including RC in some. 11 In that study, SRC patients were younger, presented with a higher grade and stage compared with UC patients, and had significantly worse 3-year CSM-free rates after RC (33% vs 67%).…”
Section: Discussionmentioning
confidence: 99%